Metronomic Cyclophosphamide and Methotrexate Chemotherapy Combined with 1E10 Anti-Idiotype Vaccine in Metastatic Breast Cancer - Jorge L. Soriano; Noyde Batista; Eduardo Santiesteban; Mayté Lima; Joaquín González; Robin García; Yohanka Zarza; María V. López; Myriam Rodríguez; Jorge L. Loys; Narciso Montejo; Frank Aguirre; et al. (International Journal of Breast Cancer)
The use of low doses of cytotoxic agents continuously for prolonged periods is an alternative for the treatment of patients with metastatic breast cancer who have developed resistance to conventional chemotherapy. The combination of metronomic chemotherapy with therapeutic vaccines might increase the efficacy of the treatment. Twenty one patients with metastatic breast cancer in progression and a Karnosky index ≥60%, were treated with metronomic chemotherapy (50 mg of cyclophospamide orally daily and 2.5 mg of methotrexate orally bi-daily), in combination with five bi-weekly subcutaneous injections of 1 mg of aluminum hydroxide-precipitated 1E10 anti-idiotype MAb (1E10-Alum), followed by reimmunizations every 28 days. Five patients achieved objective response, eight showed stable disease and eight had disease progression. Median time to progression was 9,8 months, while median overall survival time was 12,93 months. The median duration of the response (CR+PR+SD) was 18,43 months (12,20–24,10 months), being higher than 12 months in 76,9% of the patients. Overall toxicity was generally mild. Metronomic chemotherapy combined with 1E10-Alum vaccine immunotherapy might be a useful therapeutic option for the treatment of metastatic breast cancer due to its potential impact on survival and patient quality of live, low toxicity and advantages of the administration.